BUILDING TRUST IN THE DIGITAL WORLD: STRENGTHENING CYBER REGULATIONS, ADDRESSING THE CHALLENGES OF SURVEILLANCE TECHNOLOGY FROM AN ISLAMIC PERSPECTIVE: MEMBANGUN KEPERCAYAAN DI DUNIA DIGITAL: MEMPERKUAT REGULASI SIBER, MENGATASI TANTANGAN TEKNOLOGI PENGAWASAN DARI PERSPEKTIF ISLAM - Rizaldy, Wahyu Fahmi; Sopalo, Justino Ximenes Sopalo (Universitas Teknologi Surabaya, 2025)
The digital era has significantly transformed human interaction, presenting complex opportunities and challenges. Trust is a crucial pillar in building healthy and productive interactions in the digital world. However, this trust is threatened by various factors, including cybercrime, the spread of misinformation, and increasingly invasive surveillance technology. In this context, the Islamic perspective offers a comprehensive ethical framework for building trust in the digital age. This research aims to explore how Islamic principles can be applied to build trust in the digital world. The study will identify Islamic principles relevant to building trust, develop a cyber regulation framework based on Islamic values, and formulate strategies to address the challenges of surveillance technology while considering Islamic ethics and values. A normative legal approach will be employed, focusing on regulatory studies, analysis of primary and secondary Islamic legal sources, and a comparative study of cyber regulations in Muslim-majority countries. This research is expected to make a significant contribution to formulating effective, ethical, and equitable cyber regulations, as well as addressing the challenges of surveillance technology in the digital age.